MALDI-FTICR imaging mass spectrometry of drugs and metabolites in tissue - Cornett, Dale S; Frappier, Sara L; Caprioli, Richard M (Analytical chemistry (Washington), 2008)
A new approach is described for imaging mass spectrometry analysis of drugs and metabolites in tissue using matrix-assisted laser desorption ionization-Fourier transform ion cyclotron resonance (MALDI-FTICR). The technique utilizes the high resolving power to produce images from thousands of ions measured during a single mass spectrometry (MS)-mode experiment. Accurate mass measurement provides molecular specificity for the ion images on the basis of elemental composition. Final structural confirmation of the targeted compound is made from accurate mass fragment ions generated in an external quadrupole-collision cell. The ability to image many small molecules in a single measurement with high specificity is a significant improvement over existing MS/MS based technologies. Example images are shown for olanzapine in kidney and liver and imatinib in glioma.